Pengabdian Mahasiswa KKN-T Universitas Palangka Raya Kelompok 87 di Desa Tambun Raya Kecamatan Basarang Kabupaten Kapuas Provinsi Kalimantan Tengah - Hendrik Suryadi; Rts Sherly Dwijayanti; Arini Eka Jaya Prastiti; Susi Susanti; Yuni Lessari; Dimas Fathur Rahman; Maya Jovita; Lala Yetriana; Indah Nurvindyanti; Patiar Sitompul; Ruth Maoeli Lorenza Damanik; Aloysia Hermanita; Wulandari Wulandari; Ardianto Ardianto; Seilia Pebrioni Seda (Lembaga Pengembangan Kinerja Dosen, 2024)
Real Work Lecture Activities (KKN) are an important component of higher education programs which aim to apply students' knowledge, skills and attitudes in real contexts in society. This research aims to bring Palangka Raya University closer to the community, assist the government in improving the welfare of MSMEs, and increase community involvement in preventing stunting in toddlers. Apart from that, this activity aims to improve the level of education and skills of children, strengthen literacy understanding, and introduce the public to an understanding of livestock. The method used in this research is Descriptive Qualitative. The results of the research show positive Regular Thematic Real Work Lecture Activities aim to provide empirical experience to students in solving community problems and fulfilling thematic demands of the LPPM. As agents of change, students in Tambun Raya Village have the opportunity to interact directly with local social and environmental realities.